Factor Determinants of breast cancer : Systematic Literature Review - Eka Ratnasari; Ajeng Hayuning Tyas; Rizki Dyah Haninggar; Wahida Wahida; Rachmawati Rahim; Aticeh Aticeh (International Forum of Researchers and Lecturers, 2025)
Breast cancer is a highly prevalent disease and the leading cause of death in women worldwide. The determinants of breast cancer are multifactorial, including genetic, hormonal, environmental, and lifestyle factors. Breast cancer remains one of the significant global health challenges, with a growing burden of disease in both developed and developing countries. Based on recent data, it accounts for about 25% of all cancer cases in women worldwide (Sung et al., 2021). In Indonesia, breast cancer ranks first in cancer prevalence with an incidence rate of 42.1 per 100,000 population (MOH RI, 2022). This phenomenon requires a comprehensive understanding of the various determinant factors that play a role in the pathogenesis of this disease. The aim of this study was to analyze the determinant factors of breast cancer through Systematic Literature Review (SLR) of 8 national google schollar journals and 7 international pubmed journals.